Non-destructive quality assessment of tomato fruit using differential absorbance technique - Rahman, MA; Islam, MN; Nasrin, TAA; Begum, MM (International Journal of Agricultural Research, Innovation and Technology, 2020)
A rapid and non-destructive assessment of quality parameters in tomatoes was evaluated using a portable differential absorbance (DA) meter in order to accurately establish optimum harvest maturity. A commercial tomato variety cv. ‘BARI Tomato-8’ grown in the summer season of Bangladesh was used in this study. Different quality parameters including fruit skin colour, tissue firmness, chlorophyll contents, ascorbic acid, total soluble solids (TSS), titratable acidity and pH of tomatoes were determined using standard reference methods. Correlation analysis was performed to determine the relationship between the difference in absorbance index (IDA) and fruit quality parameters. The correlation coefficients showed good ability in estimating the hue angle, chlorophyll contents, titratable acidity and firmness of tomatoes showing ‘r’ values of 0.93, 0.91, 0.91 and 0.92-0.94, respectively. However, the changes of ascorbic acid contents and TSS of tomatoes did not follow the linear model during fruit maturation. Thus, the DA meter could most accurately predict the major quality attributes and may be used as an efficient technique for in-plant non-destructive assessment of tomato fruit qualities. Int. J. Agril. Res. Innov. Tech. 9(2): 42-50, December 2019